Barriers to Building Information Modeling from an Individual Perspective in the Chinese Construction Industry: An Extended Unified Theory of Acceptance and Use of Technology - Wenfan Zhang; Jintao Li; Zhengwei Liang (Buildings, 2023)
Building information modeling (BIM) is a crucial information technology that promotes the transformation and upgrading of the construction industry. It has been widely used in various stages of construction projects, including design, construction, and operation. However, BIM technology still faces numerous obstacles in practice. From the perspective of construction practitioners, this study constructs a structural equation model to explore the obstacles encountered by construction practitioners in the process of applying BIM technology. Task–technology fit, effort expectancy, performance expectancy, user trust, and facilitating conditions can significantly improve practitioners’ behavioral intention, with task–technology fit having the most significant impact on behavioral intention. Facilitating conditions and behavioral intention significantly affect usage behavior, while perceived cost does not significantly affect behavioral intention. The multiple-group analysis found that in the path of performance expectancy on behavioral intention, males have a significant effect while females do not; in the path of facilitating conditions on behavioral intention, higher education levels have a significant effect while lower education levels do not; in the path of facilitating conditions on behavioral behavior, lower usage time has a significant effect while higher usage time does not. Suggestions for promoting the application of BIM technology are proposed in this article to improve its utilization rate. This study provides more perspectives and ideas for future research on BIM diffusion.